Spatial cournot oligopoly with vertical linkages - Rocha, André (2022)
This paper examines the equilibrium of location of N vertically-linked firms. In a spatial economy composed of two regions, a monopolist firm supplies an input to N consumer goods firms that compete in quantities. It was concluded that, when there are increases in the transport cost of the input, downstream firms prefer to agglomerate in the region where the upstream firm is located, in order to obtain savings in the production cost. On the other hand, increases in the general transport cost or in the number of downstream firms lead to a dispersion of these firms, in order to reduce competition and locate closer to the final consumer.